1996
DOI: 10.1099/13500872-142-11-3275
|View full text |Cite
|
Sign up to set email alerts
|

Proline biosynthesis in Streptococcus thermophilus: characterization of the proBA operon and its products

Abstract: The presence of proline in the medium was not essential for growth of Streptococcus thermophilus, indicating that there is a proline biosynthetic pathway in this organism. Genetic and biochemical analysis identified and characterized this pathway. Two genes, designated pmB and pmA, were cloned, sequenced and characterized. Biochemical analysis of the pmB-and pmA-encoded enzymes showed that the proline biosynthetic pathway of s 8 thennophilus is similar t o the one previously described in Escherichia coli. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 38 publications
(12 reference statements)
0
34
0
Order By: Relevance
“…Genomic analysis of S. thermophilus has revealed that it has maintained the capacity to synthesize several amino acids throughout evolution (16). Despite the relevance of amino acid biosynthetic pathways in milk adaptation of S. thermophilus, only the functionality of genes involved in branched-chain-amino-acid, proline, and glutamine biosynthesis was experimentally investigated in this species (13,20,24).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genomic analysis of S. thermophilus has revealed that it has maintained the capacity to synthesize several amino acids throughout evolution (16). Despite the relevance of amino acid biosynthetic pathways in milk adaptation of S. thermophilus, only the functionality of genes involved in branched-chain-amino-acid, proline, and glutamine biosynthesis was experimentally investigated in this species (13,20,24).…”
Section: Resultsmentioning
confidence: 99%
“…Some S. thermophilus strains appear auxotrophic for at least four amino acids, Glu, Cys, His, and Met, while other lactic acid bacteria are known to be more exigent (16,19). The relevance of the amino acid biosynthetic pathways for the metabolism of S. thermophilus have been investigated for branched-chain amino acids, proline, and glutamine (13,20,24). S. thermophilus genome analysis has revealed a relatively high conservation of functional amino acid biosynthetic genes, which might reflect the importance of amino acid synthesis for the growth of this species in milk (2,16).…”
mentioning
confidence: 99%
“…To determine the first transcribed nucleotide, total RNA extracted from cells grown in the presence or in the absence of benzaldehyde and harvested at 0.3 OD 600 units was subjected to primer extension analysis as described in Limauro et al (38), using the primer 5Ј-GGTACTGAAATGA GGTAAAGGGG-3Ј, annealing from position ϩ160 to position ϩ139 in the Sso1351 gene. The same primer was used to produce a sequence ladder by using a Sequenase version 2.0 sequencing kit (Amersham) according to the manufacturer instructions to locate the products on 6% urea-polyacrylamide gel.…”
Section: Methodsmentioning
confidence: 99%
“…Streptococcus thermophilus is able to synthesize several amino acids Limauro et al, 1996). This bacterium is therefore much less nutritionally demanding than other lactic acid bacteria (Bellengier et al, 1997;Chervaux et al, 2000;Hebert et al, 2000;van Niel & HahnHägerdal., 1999).…”
Section: Introductionmentioning
confidence: 99%